2016
DOI: 10.1007/s00345-016-1923-2
|View full text |Cite
|
Sign up to set email alerts
|

Oncological outcomes of minimally invasive partial versus minimally invasive radical nephrectomy for cT1-2/N0/M0 clear cell renal cell carcinoma: a propensity score-matched analysis

Abstract: PN and RN for patients with cc-RCC larger than 7 cm provided equivalent oncologic outcomes. Safety and reproducibility of our findings should be further investigated in larger multicentric cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
2
28
1
Order By: Relevance
“…T a g g e d E n d T a g g e d P Keywords: Robotic partial nephrectomy; Upstaging; Outcomes; PredictorsT a g g e d E n d T a g g e d H 1 1. IntroductionT a g g e d E n d T a g g e d P The exponential increase in early detection of kidney cancer has dramatically changed its management over the past 2 decades, and partial nephrectomy (PN) has replaced radical nephrectomy as standard surgical treatment for T1 disease [1,2]. A paradigm shift towards PN was also observed in the management of T1b and T2 renal masses [3−5].…”
mentioning
confidence: 99%
“…T a g g e d E n d T a g g e d P Keywords: Robotic partial nephrectomy; Upstaging; Outcomes; PredictorsT a g g e d E n d T a g g e d H 1 1. IntroductionT a g g e d E n d T a g g e d P The exponential increase in early detection of kidney cancer has dramatically changed its management over the past 2 decades, and partial nephrectomy (PN) has replaced radical nephrectomy as standard surgical treatment for T1 disease [1,2]. A paradigm shift towards PN was also observed in the management of T1b and T2 renal masses [3−5].…”
mentioning
confidence: 99%
“…To date, partial nephrectomy is recommended as the preferred option for T1 tumours, if it is technically feasible 2731 . There are no differences in terms of surgical radicality, cancer-specific survival and overall survival between open, laparoscopic or robot-assisted radical nephrectomy 32 .…”
Section: Management Of Localized Diseasementioning
confidence: 99%
“…2 An analysis from Italy showed no significant difference in metastasis-free survival, local recurrence-free survival, CSS, and OS between PN and RN patients. 3 On the contrary, another report suggested that patients over 65 years who undergo PN have longer OS than those who undergo RN. 4 In terms of surgical complications, the European Organization for the Research and Treatment of Cancer (EORTC) showed that PN was associated with slightly higher complication rates compared to RN, while PN was found to be an acceptable treatment for patients with small RCC.…”
Section: Introductionmentioning
confidence: 99%